Semi-dynamic geocentric datum for positional accuracy and reliability in Malaysia - Mohd. Shariff, Noor Suryati (2018)
Land movements caused by the Earth's natural systems such as tectonic motion and earthquakes have a huge impact on the geodetic datum. The geodetic reference stations that are being used as fiducial points for realizing and maintaining the geodetic datum may shift positions. In a long term, the geodetic datum may suffer more severe coordinate shifts, ultimately resulting in non-geocentric position. The national geodetic datum of Malaysia, the Geocentric Datum of Malaysia (GDM2000), is realised as a static datum which is aligned to the International Terrestrial Reference Frame 2000 (ITRF2000) at epoch January 2000. However, ITRF is currently in version 2014 and Malaysia has experienced several land movements as a result of tectonic motion (secular) and earthquakes (non-secular). This study aims to provide the components needed to enhance the accuracy and reliability of the geodetic datum of Malaysia, outlined in three objectives. First, to investigate the spatio-temporal domain of land deformation in Malaysia. Second, to develop a land deformation model based on secular and non-secular land deformation of Malaysia. Third, to design an appropriate mechanism for the implementation of a semi-dynamic datum in Malaysia and to validate its accuracy over time. In order to achieve these objectives, three phases of methodology have been conducted. In phase one, time series analysis of selected Malaysia Real-time Kinematic Network (MyRTKnet) stations positions has been carried out using linear least squares regression technique. The second phase involves the development of a deformation model using the interpolation approach for secular model and second degree polynomial method for the post-seismic decay model. The third phase provides a timeline for implementing a semi-dynamic datum that consists of information about the applicable epoch and the respective sub-models. In addition, transformation between the new datum GDM2000 at epoch 2009.3055 and the existing datum GDM2000 is generated using the geographic offset method. Based on the time series analysis, it was found that the secular motion of Malaysia can be classified into two periods of time which are 2008-2011 and 2012-2014 and the deformation models for Peninsular Malaysia and East Malaysia have to be separated due to different velocity vectors. Results from assessment of the secular deformation model have found that millimetre-level accuracy can be achieved, i.e. below 6 mm in the horizontal position. For the non-secular deformation model, centimetre-level accuracy can be achieved, i.e. below 7 cm in the horizontal position. It is expected that with the positional accuracy results obtained in this study, it demonstrates the feasibility of implementing a semi-dynamic geocentric datum in Malaysia, thus achieving a reliable position over time.